Facial Expressions, Emotions, and Sign Languages - Elliott, Eeva A.; Jacobs, Arthur M. (Frontiers in Psychology, 2013)
Facial expressions are used by humans to convey various types of meaning in various contexts. The range of meanings spans basic possibly innate socio-emotional concepts such as ‘surprise’ to complex and culture specific concepts such as ‘carelessly’. The range of contexts in which humans use facial expressions spans responses to events in the environment to particular linguistic constructions within sign languages. In this mini review we summarize findings on the use and acquisition of facial expressions by signers and present a unified account of the range of facial expressions used by positing three dimensions; semantic, iconic and compositional.